2023
DOI: 10.1108/jfbm-04-2023-0056
|View full text |Cite
|
Sign up to set email alerts
|

How family firm advisors understand their clients: a mixed-methods analysis of social capital signaling in web-based marketing

Robert Randolph,
Eric Kushins,
Prachi Gala

Abstract: PurposeDespite similarities, research across family business and business advising forwards contradictory conclusions when considering family business advising. The authors seek to integrate these literature and in doing so uncover both the hurdles facing family business advisors attempting to adapt tools developed in corporate advising to the family business context as well as the potential for greater integration of these streams in ways that contribute to both family business and advising research and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
1
0
0
Order By: Relevance
“…It means that the next significant practical implication for FAs is the necessity to concentrate on creating a diversified portfolio of succession projects. This aligns with the findings of Randolph et al. (2023) who suggested that advisors' marketing through websites is not the most effective way to reach family business owners.…”
Section: Discussionsupporting
confidence: 87%
“…It means that the next significant practical implication for FAs is the necessity to concentrate on creating a diversified portfolio of succession projects. This aligns with the findings of Randolph et al. (2023) who suggested that advisors' marketing through websites is not the most effective way to reach family business owners.…”
Section: Discussionsupporting
confidence: 87%